HICOLM: High-Performance Platform of Physical Simulations by Using Low Computational Cost Methods - Fernandes, Flaviano Williams (Revista de Informática Teórica e Aplicada, 2019)
For decades, computational simulation models have been used by scientists in search for new materials with technological applications in several areas of knowledge. For this, software based on several theoretical-computational models were developed in order to obtain an analysis of the physical properties at atomic levels. The objective of this work is proposing a widely functional software to analyze the physical properties of nanostructures based on carbon and condensed systems using theories of low computational cost. Therefore, a Fortran language computational program called HICOLM was developed, whose theoretical bases are based on two commonly known models (Tight-binding and Molecular Dynamics). The physical properties of condensed systems can be obtained in the thermodynamic equilibrium in several statistical ensembles, and possible to obtain an analysis of the properties of the material and its evolution in the time-dependent on its thermodynamic conditions like temperature and pressure. Moreover, from the tight-binding model, the HICOLM program is also capable of performing a physical analysis of carbon-based nanostructures from the calculation of the material band structure.